Strategies to improve retention in randomised trials - Gillies, Katie (Cochrane Database Syst Rev, 2021)
BACKGROUND: Poor retention of participants in randomised trials can lead to missing outcome data which can introduce bias and reduce study power, affecting the generalisability, validity and reliability of results. Many strategies are used to improve retention but few have been formally evaluated. OBJECTIVES: To quantify the effect of strategies to improve retention of participants in randomised trials and to investigate if the effect varied by trial setting. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Scopus, PsycINFO, CINAHL, Web of Science Core Collection (SCI‐expanded, SSCI, CPSI‐S, CPCI‐SSH and ESCI) either directly with a specified search strategy or indirectly through the ORRCA database. We also searched the SWAT repository to identify ongoing or recently completed retention trials. We did our most recent searches in January 2020. SELECTION CRITERIA: We included eligible randomised or quasi‐randomised trials of evaluations of strategies to increase retention that were embedded in 'host' randomised trials from all disease areas and healthcare settings. We excluded studies aiming to increase treatment compliance. DATA COLLECTION AND ANALYSIS: We extracted data on: the retention strategy being evaluated; location of study; host trial setting; method of randomisation; numbers and proportions in each intervention and comparator group. We used a risk difference (RD) and 95% confidence interval (CI) to estimate the effectiveness of the strategies to improve retention. We assessed heterogeneity between trials. We applied GRADE to determine the certainty of the evidence within each comparison. MAIN RESULTS: We identified 70 eligible papers that reported data from 81 retention trials. We included 69 studies with more than 100,000 participants in the final meta‐analyses, of which 67 studies evaluated interventions aimed at trial participants and two evaluated interventions aimed at trial staff involved in retention. All studies were in health care and most aimed to improve postal questionnaire response. Interventions were categorised into broad comparison groups: Data collection; Participants; Sites and site staff; Central study management; and Study design. These intervention groups consisted of 52 comparisons, none of which were supported by high‐certainty evidence as determined by GRADE assessment. There were four comparisons presenting moderate‐certainty evidence, three supporting retention (self‐sampling kits, monetary reward together with reminder or prenotification and giving a pen at recruitment) and one reducing retention (inclusion of a diary with usual follow‐up compared to usual follow‐up alone). Of the remaining studies, 20 presented GRADE low‐certainty evidence and 28 presented very low‐certainty evidence. Our findings do provide a priority list for future replication studies, especially with regard to comparisons that currently rely on a single study. AUTHORS' CONCLUSIONS: Most of the interventions we identified aimed to improve retention in the form of postal questionnaire response. There were few evaluations of ways to improve participants returning to trial sites for trial follow‐up. None of the comparisons are supported by high‐certainty evidence. Comparisons in the review where the evidence certainty could be improved with the addition of well‐done studies should be the focus for future evaluations.